Mourning, linguistic improvisation and shared histories in Marlene van Niekerk's Agaat - Symmonds, Tracy (My University, 2013)
INTRODUCTION Certain novels ensnare their readers. Like the „wag „n bietjie‟ thorn tree or Ziziphus mucronata with its vicious paired thorns, one straight thorn pointing forwards to the future, the other pointing backwards, the reader is hooked, perhaps wounded, unable to walk away unscathed, but caught up and forced to reflect a moment. In all likelihood, there is a breaking of skin and perhaps a scarring, a haunting, a reckoning with loss, akin to the tree‟s association with burial. Such a novel is Marlene van Niekerk‟s Agaat, translated by Michiel Heyns (2006). Staged at the bed-crypt of the dying matriarch Milla, who now has become prone, paralysed and voiceless, the novel exhumes, through a slow, almost wake-like recall, the complexities of her relationship with Agaat, her one-time daughter, now servant. Memory and mourning are fundamental to Agaat and become manifest in Agaat‟s ruthless reading aloud of Milla‟s diaries, which often vindictively edits, annotates and paraphrases Milla‟s rendition of Agaat‟s life. What emerges with every re-reading is the brutality of an abusive relationship with its history of trauma, inequality and racism, evocative of T.S. Eliot‟s words that frame the English translation of the novel, “And last, the rending pain of re-enactment”. This might have the effect of a thorn being driven progressively deeper in an urge to escape further wounding, with a result akin to Judith Butler‟s belief that in mourning “we‟re undone by each other” (2004: 23). Yet at this very site of trauma, Van Niekerk appears to effect a poignancy and intermittent affection in the improvised communication between master and servant. The intricate shadow play which arises points to the location of a potential space of opportunity, begging the question Van Niekerk herself poses in an interview: “Can a person with the tools of the master, break the master‟s house down?” (2008: 48) The project of the novel is prophetically captured in Milla‟s words: “The remembering, the reading, the dying, the song” (p. 212). This essay offers a reading of the novel as an examination of inheritance, memory, haunting and mourning, both psychoanalytically in the distorted relations between Milla and Agaat, and linguistically through the haunted language she and Agaat construct. Milla herself merges these strands in her opening statement: “It‟ll be the end of me yet, getting communication going” (p. 9). Firstly, in my psychoanalytic investigation, I intend to consider the usefulness to a reading of Agaat of Freud‟s analysis of mourning and melancholia and of Abraham and Torok‟s extension of this, according to which the child (Agaat) internalises the secrets buried in discourses she hears, having a direct empathy with unconscious or denied material from the parental object (Milla). In this process the child becomes the bearer of a phantom, a radically alien, uninvited other, buried within her unconscious. Agaat‟s task might, from this perspective, be seen as putting unspeakable and silenced secrets into words (or perhaps other symbolic forms, like embroidery). This approach links to André Green‟s concept of the dead mother, which is “an imago in the child‟s mind, following maternal depression, brutally transforming a living object, which was a source of vitality for the child, into a distant figure, toneless, practically inanimate” (Green, 1999: 2). Consideration will also be given to Derrida‟s theory of ghostly voices, which he describes as the trans-generational spectres in every text that bear the undisclosed traumas of their predecessors. In this sense, both Milla‟s diaries and the novel itself contain more than they know: the limitless traces of other words which lie beyond simple truth or falsehood. Central to the task of understanding the process of mourning in the novel is a close reading of the language Agaat and Milla invent to negotiate their histories through the re-iteration and appropriation of the diaries: a unique communication at once angry, vengeful, obsessive, compassionate and poignant. In the scholarly criticism on Agaat referenced in the bibliography, there appears to be a dearth of in-depth textual analysis on Agaat. This is understandable in a text that is both vast and multi-layered. An analysis of the role of language in the novel must, however, explore at least part of the text in detail in order to gain insight into the texture of the linguistic game that is played between the two main characters. My second broad aim, therefore, is to offer such a reading of chapter sixteen, a seminal chapter where Agaat and Milla‟s attempts at communication are foregrounded. In conclusion, or rather in speculation, I will attempt to unravel some of the implications of the interpersonal improvisation between the two women. This includes the question whether Milla‟s departure may inaugurate the end of Agaat‟s trauma, or whether with the loss of Agaat‟s internal support, her mourning may be interminable. Levinas‟ proposition that death is a relation with the other might be instructive in this regard (quoted in Davis, 2007: 117). If Agaat and Milla‟s shared „language‟ comes to terms with the past, there may be a possibility of a new relationship, beyond the play of phantoms. This invites speculation on whether the novel offers any kind of closure. If Agaat has „written back‟ to Milla there may be a sense, as Agaat and Milla‟s experience is reworked and reworded, of Proust‟s project to retrieve and „conclude‟ lived experience through the act of writing. From this perspective, Van Niekerk‟s novel could also be read as a radical commentary on productive lacunae in post-apartheid South Africa. On the other hand, given the density of the text and the traumas it uncovers, the innovative communication may be more indicative of shadows and hauntings, in a closed-circuit version of shadow boxing that offers little prospect of a new dispensation.
Thesis (M.A.)--University of the Witwatersrand, Faculty of Humanities, School of Language and Literature Studies (Modern and Contemporary Literature), 2013